Effect of Precirol ATO5 concentration and twin-screw melt granulation temperature on the physical properties of ascorbic acid granules - Valentyn Mohylyuk; David Jones; Shu Li; Yalin Ding; Gavin Patrick Andrews (University of Huddersfield Press, 2022)
The pharmaceutical industry has a growing interest in continuous manufacturing, particularly for high-volume dosage forms such as solid oral tablets. This is driven by the obvious benefits such as small footprint, batch size flexibility, the relative simplicity of scale-up and process control. Tablets are the most popular solid dosage form, while batch granulation is one of the most often used technologies in tablet manufacturing. Using ascorbic acid as a model, we show the possibility of producing granules and tablets with a sustained-release profile using three technological operations: mixing, continuous melt-granulation, and tabletting.